Hubungan Antara Persepsi Stunting Remaja Putri Dengan Dietary Habits - Rizqi Nursasmita; Ni Putu Ayu Kristianti; Andi Mayasari Usman (Health and Technology Journal (HTechJ), 2024)
Stunting is a chronic nutritional problem caused by a lack of nutritional intake over a long period of time. Dietary habits are healthy and balanced eating patterns that help control blood glucose and balance body weight. The cause of the increase in stunting rates is due to the lack of knowledge in adolescents who will become future mothers about good nutritional intake, due to a poor economy that makes it difficult for people to get nutritious food to fulfil children's nutrition during their growth and development. For this reason, stunting prevention can be done since adolescence. This study aims to determine the relationship between perceptions of stunting and dietary habits of adolescent girls at SMA Nurul Falah North Jakarta. This study used a quantitative research design with a cross sectional approach. The sample in this study were 76 female students. Samples were taken with simple random sampling technique. The instrument used was a stunting perception questionnaire and dietary habits and validity and reliability tests were carried out, obtained the results of the stunting perception questionnaire (0.847) and the dietary habits questionnaire (0.645). The results of this study indicate that there is a relationship between perceptions of stunting and dietary habits of adolescent girls with a p-value of 0.001 and a value of r=0.376. There is a relationship between perceptions of stunting and dietary habits of adolescent girls at SMA Nurul Falah Jakarta. It is hoped that the school can provide education about stunting and prevention methods that adolescents can do to break the chain of stunting in the future and provide education on how to carry out a good and healthy dietary habits programme.